Study of various gynaecological problems and reproductive health awareness amongst adolescents at a rural setup in central India - Samarth, Snehal; Inamdar, Saunitra; Hariharan, Chella; Kalyani, Kanika R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adolescent problems are increasing over the years and need special consideration. We, as health care providers, need to focus on young people as investing in their health today will reap rich rewards tomorrow. Methods: All the adolescents presenting with various gynaecological problems were evaluated by detailed history taking and thorough clinical examination after taking an informed consent and explaining them our objective. After examination, adolescent girls were given education by means of slide show about menstruation, care during menses, nutritional diet and prevention of anaemia. Results: Majority of adolescents had regular menstrual pattern. Oligomenorrhoea was the most prevalent abnormality of menstrual pattern in these adolescents. 15.58% adolescents had presented with breast problems like mastalgia, lump in breast, etc. Majority of adolescents studied were aware of the physical signs of puberty (77.25%) and HIV (74.14%). But very few adolescents were aware of the physiology involved in menstruation. Around half of all the adolescents were seen to follow proper menstrual hygiene. Conclusions: Healthy adolescence, the need of the hour.